Effect af rare earth impurities on the α - γ transition in metallic Ce - Alascio, Blas Rafael; López, A.; Olmedo. C. F. E (Instituto de Física "Dr. José A. Balseiro". Universidad Nacional de Cuyo, 1971)
Fil: Alascio, B. R. Comisión Nacional de Energía Atómica; Argentina